2011
DOI: 10.1152/jn.01069.2010
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance adaptation reveals the involvement of the dorsomedial stream in hand orientation for grasping

Abstract: Reach-to-grasp actions require coordination of different segments of the upper limbs. Previous studies have examined the neural substrates of arm transport and hand grip components of such actions; however, a third component has been largely neglected: the orientation of the wrist and hand appropriately for the object. Here we used functional magnetic resonance imaging adaptation (fMRA) to investigate human brain areas involved in processing hand orientation during grasping movements. Participants used the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
98
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 129 publications
(107 reference statements)
11
98
0
Order By: Relevance
“…Previous studies reveal RS in some of the same parietal and frontal regions during repeated grasping (Kr贸liczak, Mcadam, Quinlan & Culham, 2008; Monaco, Cavina-Pratesi, Sedda, Fattori, Galletti & Culham, 2011; Monaco, Chen, Medendorp, Crawford, Fiehler & Henriques, 2014) or hand gestures (Chouinard & Goodale, 2009; Dinstein, Hasson, Rubin & Heeger, 2007; Hamilton & Grafton, 2009). While several of these studies distinguished motor- from visually-driven RS (Chouinard & Goodale, 2009; Kr贸liczak, et al, 2008; Monaco, et al, 2011; Monaco, et al, 2014), it has remained unclear whether motor-driven effects reflected the repetition of planning/selection, execution-related processes, or both. Our Condition * Congruency interaction with Plan RS > Rule RS revealed effects in left SMg, bilateral cSPL, as well as the left Cerebellum.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies reveal RS in some of the same parietal and frontal regions during repeated grasping (Kr贸liczak, Mcadam, Quinlan & Culham, 2008; Monaco, Cavina-Pratesi, Sedda, Fattori, Galletti & Culham, 2011; Monaco, Chen, Medendorp, Crawford, Fiehler & Henriques, 2014) or hand gestures (Chouinard & Goodale, 2009; Dinstein, Hasson, Rubin & Heeger, 2007; Hamilton & Grafton, 2009). While several of these studies distinguished motor- from visually-driven RS (Chouinard & Goodale, 2009; Kr贸liczak, et al, 2008; Monaco, et al, 2011; Monaco, et al, 2014), it has remained unclear whether motor-driven effects reflected the repetition of planning/selection, execution-related processes, or both. Our Condition * Congruency interaction with Plan RS > Rule RS revealed effects in left SMg, bilateral cSPL, as well as the left Cerebellum.…”
Section: Discussionmentioning
confidence: 91%
“…RS paradigms are widely used in fMRI research (see, e.g., Grill-Spector et al 2006), and RS paradigms have been used successfully for the investigation of motor planning (Bernier and Grafton 2010; Hamilton and Grafton 2009; Kr贸liczak et al 2008; Majdand啪i膰 et al 2009; Monaco et al 2011; Valyear et al 2012; Van Pelt et al 2010). RS effects have been previously reported in the regions studied here (e.g., Hamilton and Grafton 2009; Kr贸liczak et al 2008; Van Pelt et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For task used in the current study, where orientation is a relevant feature, one may consider the involvement of other brain areas somehow involved in aspects of orientation coding for motor planning. Of particular interest is the monkey area V6(A) (Fattori et al 2010;Galletti et al 2003) and its likely human homolog, the superior parietooccipital cortex (SPOC; Gallivan et al 2009;Monaco et al 2011), both of which have been shown to be important for wrist orientation while grasping. Further studies are necessary not only to show the exact mechanism that drives the perceptual changes due to action preparation, but also to identify these other motor areas involved in the general mechanism of action-modulated perception.…”
Section: Discussionmentioning
confidence: 99%